A stereoselective vinylogous aldol reaction of tetronamides and the synthesis of rubrolides and beta- substituted butenolides - Karak, Milandip (2017)
Butenolides are α, -unsaturated lactone and are found in many natural and unnatural products with diverse biological properties. Owing to the prevalence of the substituted butenolides, much effort has been directed towards developing efficient methodologies for their synthesis and transformations. Among them, stereoselective access of the -substituted butenolide derivatives by utilizing the concept of vinylogy, which usually involves the carbon– carbon formation with an appropriate electrophile at the -position of butenolides, has triggered increasing interest. This thesis presents an efficient, simple, scalable and direct stereoselective vinylogous aldol reaction (VAR) of -aminosubstituted butenolides (tetronamides) with aldehydes. In addition, this thesis also describes the total syntheses of butenolide core bearing marine natural metabolites, rubrolides by using a highly regioselective late-stage bromination from appropriate intermediates, and apprises a facile reductive dehalogenation of α-halo- -substituted butenolides. An introduction to the general background, including versatile synthetic strategies, total syntheses, and biological properties of substituted butenolides is documented in Chapter 1. It is followed by an illustration of selected methods for construction of the butenolide core. Also discussed are the various methods for preparation of some selected natural products which either possess a butenolide core or synthesized from butenolide building blocks. Finally, some synthetic butenolide derivatives are described which are recently marketed as either medicines or agrochemicals. The results of the stereoselective VAR of tetronamides are compiled in Chapter 2. The described procedure, is simple and scalable, works well with both aromatic and aliphatic aldehydes, and affords mainly the corresponding syn-aldol adducts. In many cases, the latter are obtained essentially free of their anti-isomers in high yields. A detailed computational study was also carried out to establish the reaction mechanism. The experimental and computational studies suggest that the observed diastereoselectivity arises through anti–syn isomer interconversion, enabled by an iterative retro-aldol/aldol reaction. In Chapter 3, the crystal structures of several tetronamide aldol products with two stereocenters are described. Those compounds revealed conformational and supramolecular trends with the substitution pattern of a side aromatic/ heteroaromatic ring. The major contribution of this study concerns the control over the molecular conformation of tetronamide aldolates bearing several rotatable bonds and the high conformational freedom through the substitution pattern of a single ring. The first total syntheses of the marine natural products rubrolides I and O and some of their unnatural congeners are reported in Chapter 4. A versatile late-stage bromination strategy allowed functionalization of the aromatic rings in a highly regioselective fashion, enabling rapid access to the target rubrolides from common precursors. Next, the regioselective chlorination was also applied to the preparation of biologically important synthetic analogous of rubrolides from easily accessible precursors. In Chapter 5, a binary palladium catalyzed reductive dehalogenation of α-halo- -substituted butenolides is documented. The synthetic procedure allowed rapid access to the -substituted butenolides under mild conditions with high yields and excellent regioselectivity. In addition, a protecting group free step-economical synthesis of rubrolides E, F and γ”-bromorubrolide F has been reported by employing this protocol.